INCREASED SENSORY QUALITY AND CONSUMER ACCEPTABILITY BY FORTIFICATION OF CHOCOLATE FLAVORED MILK WITH OAT BETA GLUCAN - CHATTERJEE, BANDANA; PATEL, TINKAL (International Journal of Clinical and Biomedical Research, 2016)
Objective: This study is done in respect to develop a milk based product having both the properties of milk and oat beta glucan. The objective of the study is to analyze the stability, texture and overall acceptance of flavored milk with oat beta glucan and to assess the processing parameters in order to increase the stability. Materials & Methods: In this study two methods have been used. First method is one stage processing in which beta-glucan (3%) was added simultaneously with carrageenan and In Second method, oat beta-glucan is not added and chocolate milk is made by carrageenan and the other dry ingredients only. Result is tasted by sensory evaluation, texture properties and viscosity. Results: In both the studies, The mouthfeel and viscosity is better in chocolate FM fortified with oat beta glucan. Conclusion: In this study we use 3% oat beta-glucan for fortification of the chocolate milk. Sensory evaluation is carried out for consumer preference and the texture and viscosity is also measured. chocolate FM with oat beta-glucan has improved mouthfeel, viscosity and fortified with fiber milk. By adding oat beta-glucan we can claim points about Fiber as per FSSAI Guidelines also.